Design and exploration of C-3 benzoic acid bioisosteres and alkyl replacements in the context of GSK3532795 (BMS-955176) that exhibit broad spectrum HIV-1 maturation inhibition. (15th March 2021) - Swidorski, Jacob J.; Jenkins, Susan; Hanumegowda, Umesh; Parker, Dawn D.; Beno, Brett R.; Protack, Tricia; Ng, Alicia; Gupta, Anuradha; Shanmugam, Yoganand; Dicker, Ira B.; Krystal, Mark; Meanwell, Nicholas A.; et al.
Graphical abstract: Abstract: GSK3532795 (formerly BMS-955176) is a second-generation HIV-1 maturation inhibitor that has shown broad spectrum antiviral activity and preclinical PK predictive of once-daily dosing in humans. Although efficacy was confirmed in clinical trials, the observation of gastrointestinal intolerability and the emergence of drug resistant virus in a Phase 2b clinical study led to the discontinuation of GSK3532795. As part of the effort to further map the maturation inhibitor pharmacophore and provide additional structural options, the evaluation of alternates to the C-3 phenyl substituent in this chemotype was pursued. A cyclohexene carboxylic acid provided exceptional inhibition of wild-type, V370A and ΔV370 mutant viruses in addition to a suitable PK profile following oral dosing to rats. In addition, a novel spiro[3.3]hept-5-ene was designed to extend the carboxylic acid further from the triterpenoid core while reducing side chain flexibility compared to the other alkyl substituents. This modification was shown to closely emulate the C-3 benzoic acid moiety of GSK3532795 from both a potency and PK perspective, providing a non-traditional, sp 3 -rich bioisostere of benzene. Herein, we detail additional modifications to the C-3 position of the triterpenoid core that offer effective replacements for the benzoic acid of GSK3532795 and capture the interplay between these new C-3 elements and C-17 modifications that contribute to enhanced polymorph coverage.